Templates Synthesis of Oxovanadium(IV) Complexes with Tetradentate 16-Membered N6 Macrocyclic Ligands - Yadav, H.S. (Asian Journal of Chemistry, 2010)
The macrocyclic complexes [VO(mac)] (where mac = 16-membered macrocyclic ligands derived by condensation of 2,6-diaminopyridine with β-diketones) have been synthesised by in situ method using oxovanadium(IV) cation as template. The complexes have been characterized on the basis of elemental analyses, electrical conductance, magnetic susceptibility measurements and spectral (infrared and electronic) data. The macrocyclic ligands act as tetradentate dianions and oxovanadium(IV) complexes are five co-ordinated. Pyridine nitrogens remain uncoordinated.